Iron deficiency amongst university graduates; prevalence, diagnosis, and iron consumption - Chaudhry, Gul-E-Saba; Zeenia; Md Akim, Abdah; Sung, Yeong Yik; Tengku Sifzizul, Tengku Muhammad (Medknow Publications, 2023)
Anemia is a worldwide epidemic, and iron deficiency is a leading cause of anemia. We used anthropometric measurements and a multisectioned questionnaire to get as much information about diet as possible. The blood was taken to determine their iron stores via a test measuring their hemoglobin (Hb). Iron deficiency was examined alongside gender, body mass index, family history, the variety and quantity of the foods eaten, the frequency of eating each of the five main food groups, and the prevalence of anemia. The correlation between dietary factors like grains, protein, dairy, vegetables, and fruits, and iron levels was also performed. The percentage of underweight men ranged from 2% to 14%, while 6% to 4% and stages II and III obesity were each found among men. Ten percent of men with normal blood iron levels were found to have mild iron deficiency. When it comes to women, 32% were underweight while only 6% were in stage I obesity. Although supplement use can improve health by lowering the risk of problems associated with iron deficiency, it can also cause gastrointestinal distress in some people. It can raise the supplement's already high risk of kidney or gallstone formation. Therefore, a study examining the correlation between iron deficiency anemia and specific nutrients could raise consciousness about the importance of eating healthfully and maintaining proper nutrient levels in the body. Scientific research and medical diagnosis will benefit from this as well.